Compensatory Breeding in Years Following Drought in a Desert-Dwelling Cooperative Breeder - Bourne, Amanda R.; Cunningham, Susan J.; Spottiswoode, Claire N.; Ridley, Amanda R. (Frontiers in Ecology and Evolution, 2020)
Variation in weather patterns can influence reproductive effort and success not only within but also between breeding seasons. Where environmental conditions can be highly variable between years, the weather, and particularly extreme weather events such as heat waves and droughts, may exert a strong influence on reproductive effort (number of breeding attempts) and success (number of surviving young) from one breeding season to the next. We used a 15-year dataset for a cooperatively-breeding bird, the southern pied babbler Turdoides bicolor, to determine the impact of high temperatures and drought on reproductive effort and success. We tested the influence on reproductive effort and success of mean daily maximum air temperature and drought both within a breeding season, to determine the relative importance of current conditions, and during the previous breeding season, to determine the relative importance of compensatory effects in response to prior conditions. Reproductive effort and success were lower during breeding seasons characterised by drought, and higher in the breeding seasons that followed droughts, but were not predicted by mean daily maximum temperatures measured over the full length of the breeding season. We provide evidence of compensatory breeding following drought in a bird species endemic to a semi-arid ecosystem and suggest that compensatory mechanisms may be an important part of both long-term population persistence and post-drought population recovery.